Efficacy of Antiresorptive Treatment in Osteoporotic Older Adults: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Cedeno-Veloz, Bernardo Abel; Erviti Lopez, J.; Gutiérrez-Valencia, M.; Leache Alegría, L.; Saiz, L.C.; Rodríguez García, A.M.; Sánchez Latorre, M.; Ramírez Vélez, R.; Izquierdo, M.; Martínez-Velilla, N. (The Journal of nutrition, health & aging, 2022)
To investigate concerns surrounding the benefits of antiresorptive drugs in older adults, a systematic review was carried out to evaluate the efficacy of these treatments in the prevention of osteoporotic hip fractures in older adults. A systematic review and meta-analysis of randomized clinical trials. Older adults ≥65 years with osteoporosis, with or without a previous fragility fracture. Studies with cancer-related and corticosteroid-induced osteoporosis, participants <65 years and no reported hip fracture were not included. MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, ISI Web of Science and Scopus databases were searched. The primary outcome was hip fracture, and subgroup analysis (≥75 years, with different drug types and secondary prevention) and sensitivity analysis was carried out using a GRADE evaluation. Secondary outcomes were any type of fractures, vertebral fracture, bone markers and adverse events. The risk of bias was assessment with the Cochrane risk of bias tool. A total of 12 randomised controlled trials (RCTs) qualified for this meta-analysis, with 36,196 participants. Antiresorptive drugs have a statistically significant effect on the prevention of hip fracture (RR=0.70; 95%CI 0.60 to 0.81), but with a moderate GRADE quality of evidence and a high number needed to treat (NNT) of 186. For other outcomes, there is a statistically significant effect, but with a low to moderate quality of evidence. Antiresorptives showed no reduction in the risk of hip fracture in people ≥75 years. The results for different drug types, secondary prevention and sensitivity analysis are similar to the main analyses and have the same concerns. Antiresorptive drugs have a statistically significant effect on preventing hip fracture but with a moderate quality (unclear/high risk of bias) and high NNT (186). This small benefit disappears in those ≥75 years, but increases in secondary prevention. More RCTs in very old osteoporotic adults are needed.